Paging and scrolling: Cognitive styles in learning from hypermedia - Eyuboglu, Filiz; Orhan, Feza (WILEY, 2011)
This study investigates the navigational patterns and learning achievement of university students with different cognitive styles, on hypermedia learning environments using paging or scrolling. The global-local subscales of Sternberg's Thinking Styles Inventory, two hypermedia, one using paging, the other using scrolling, a multiple choice achievement test, and a questionnaire to collect the students' satisfaction on paging/scrolling were used as data collection tools. This study finds that the cognitive style and paging/scrolling, together or separately, neither affected the learning nor the satisfaction of learners. Students with different cognitive styles using paging or scrolling did all learn well, with no statistically significant difference. Also the navigation patterns did not seem to depend on cognitive style; that is, the frequencies of using the navigation tools were not significantly different.
Keywords: INFORMATION-SEEKING; Education & Educational Research